Carbon Nanotubes and Associated Devices 2008
DOI: 10.1117/12.792651
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Raman scattering of smallest single-walled carbon nanotubes

Abstract: We report optical properties of the smallest single-walled carbon nanotubes (SWNTs) with a diameter of only 3 Å . These ultrasmall SWNTs are fabricated in the elliptical nanochannels of an AlPO-11 (AEL) single crystal. Polarized and resonant Raman scattering unambiguously revealed that these 0.3 nm SWNTs are of (2,2) armchair symmetry. Interestingly, the (2,2) armchair tube has two metastable ground states corresponding to two slightly different lattice constants in the axial direction: one state is metallic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…13 One reason for the lack of the theoretical results is the lack of corresponding experiments. Even though single spe-cies of very narrow tubes, down to the 0.4 nm range, were grown in the channels of zeolite crystals, 14 the lack of a full set of extremely high curvature tubes prevented so far a check of the expected dramatic deviation of their electronic structure from the tight-binding results.…”
mentioning
confidence: 99%
“…13 One reason for the lack of the theoretical results is the lack of corresponding experiments. Even though single spe-cies of very narrow tubes, down to the 0.4 nm range, were grown in the channels of zeolite crystals, 14 the lack of a full set of extremely high curvature tubes prevented so far a check of the expected dramatic deviation of their electronic structure from the tight-binding results.…”
mentioning
confidence: 99%
“…In addition, previous reports have indicated that single-chirality (2,2) CNTs can be formed inside the channels of zeolite template, despite that such ultrasmall CNTs would decompose without confinement of template. 139 These results suggest that design and exploration of suitable templates or substrates that have very strong interactions with certain types of CNTs could also be an interesting approach to try besides catalyst engineering. Furthermore, the charge transfer from catalyst nanoparticles to the growing nanotube edge atoms was studied and found to play a role in enhancing the reactivity of growth edges by changing their frontier electron density, which implies that the growth active sites are strongly correlated with the structures of metal nanoparticles through charge transfer.…”
Section: Applications Of Chirality-pure Carbon Nanotubesmentioning
confidence: 99%
“…The Fermi level may be further tuned by application of pressure or electric gate voltages [12], and in addition the superconductivity of SWCNTs may be further tunable through the lateral tube-to-tube distances and bond lengths. However, the synthesis of high quality carbon nanotubes thinner than 4 Angstrom in diameter represents a challenge [13]. In addition, no theoretical model predicting the superconducting transition temperature T c of the SWCNTs accurately was reported so far, despite of numerous first principle calculations that have been reported for SWCNTs [14,15].…”
Section: Introductionmentioning
confidence: 99%